Biometric data security using joint encryption and watermarking. (4th June 2019) - Mehta, Garima; Dutta, Malay Kishore; Kim, Pyung Soo
Confidentiality and content ownership are considered to be an important aspect of security applications and therefore a joint watermarking and encryption scheme is developed. This work addresses the issue of authenticity and integrity of watermark or ownership identification by embedding biometric iris template as a watermark in a fingerprint host image. The proposed approach is a two-step approach which includes encryption and watermarking. During the encryption, iris features are encrypted using combination of FRWT with Arnold cat map while watermark embedding is done by using dual DWT-SVD scheme to improve robustness and protection of biometric security systems. Experimental results demonstrate that the proposed joint encryption and watermarking introduces efficiency, security and robustness against image processing attacks.